Organizing Bases of Youth Physical Training in the Soviet Ukraine in the 20th of the XX th Century - Hennadiy Kovalchuk (Pedagogical Discourse, 2013)
The article deals with the organizing bases of the becoming and the development of the youth physical training in the Soviet Ukraine in the 20th of the XX th century. On the principles of appropriate bibliography sources the author tried to embody the historic-pedagogical analysis of the active physical training Soviet system building up. It was accomplished with the help of the energetic government position, state party management and the Komsomol initiative on the firm ideological basis with youth following on the mass military and sport drill stipulated with the peculiarity of the social-political and economic situation in the country. Physical training and sport movement content and forms are generalized. The importance of the historic experience of the past for modern theory and practice is indicated.